Low SAR compact wideband/dual-band semicircular slot antenna structures for sub-6 GHz 5G wireless applications - Reham W. Abd-Elsalam; Hussein E. Seleem; Mostafa M. Abd-Elnaby; Amr H. Hussein (EURASIP Journal on Wireless Communications and Networking)
Abstract The design and fabrication of planar semicircular slot antennas for both wideband and dual-band sub-6 GHz 5G wireless applications are presented in this paper. A transmission line feed is included in the designed U-shaped radiating patch. To minimize the antenna size and control the bandwidth, a semicircle-defected ground structure is etched beneath the radiating patch. To allow for dual-band operation, a T-shaped stub structure is attached in the middle of the U-shaped radiating patch. If the transverse part of the T structure is connected to the two U limbs, the antenna performs as a wideband antenna (WBA). Furthermore, reducing and modifying the length of the T structure’s transverse part are equivalent to constructing a frequency tunable band-stop filter that controls the two operating frequency bands of the antenna. The design has a small footprint of (0.35λ 0 × 0.35λ 0) where λ 0 denotes the free space wavelength, peak gain, and efficiency of about 8.5 dBi and 93%, respectively. When the length of the transverse part of the T structure L B = 10.3 mm, the antenna acts as a WBA with operating frequency band from 1.8 to 6 GHz. When the length of the transverse part of the T structure is reduced to L B = 4.3 mm, the antenna is converted into a dual-band antenna with operating frequency bands from 1.8 to 3.7 GHz and from 4.05 to 5.5 GHz. In the simulations, the antenna performed adequately when both the dielectric back cover and the human head-hand model are present. The study achieved safe specific absorption rate (SAR) values that preserve good efficiencies and radiation patterns. The investigated SAR10g values at 3.3/4.5 GHz are equal to 0.121 W/kg, which are within allowable bounds. The simulations and measurements are highly matched.